Development of Interdisciplinary Views on the Energetics of Human Communicative Behavior - Деркач, Наталія (Studia Philologica, 2024)
This paper presents the results of a retrospective analysis of the scientific views on the energetics of human communicative and speech behavior. The etymology of the lexeme ‘energy’ is looked into; the definitions of the notion of ‘energy’ available in 17 lexicographic sources are analyzed, and semantic units incorporated into its lexical meaning are extracted. The analysis of their content makes it possible to define four essential features of the general scientific notion of ‘energy’ and synthesize its definition. As the energetics of human communicative behavior is traditionally seen as divided into the psychic and the physical components, its adequate description is possible only with the instruments of the integrative approach. The issues of mutual conversion of several types of energy to cater for various individual’s behavioral programs, as well as physical and physiological aspects of speech energetics have already been researched to a certain extent. Less attention has been paid to the psychic energy of a person, which nonetheless is intuitively considered to be a significant motive of any form of human activity. A concise account of historical views on the human psychic energy, nominated “prana”, “chi”, “soul”, “spirit”, “entelechy”, “energeia”, “psychic pneuma”, “animal spirits”, etc. is provided in the paper. Milestones in the research of the neurophysiological aspect of the energy supply of human communicative and speech behavior are reviewed. Special attention is paid to Freud’s description of the human psychic energy “economy” as the first full-fledged theory, capable of forming the basis for modeling the energetics of human communicative and speech behavior. Mention is made of the modern concept of “allostasis” oriented towards an anticipatory forecasting of energy needs by the organism rather than its posterior restoration upon some significant psychic events. Due to a lack of theoretical and experimental linguistic research, taking into consideration energy dynamics of the communicants’ psychic processes, a universal stochastic model of utterance generation, developed by A. Kalyta and O. Klymeniuk appears specifically promising. It could be effectively used in the development of the methodology of an experimental-phonetic study of conflict talks, typically marked with a significant level of emotional tension.